Pengembangan Mobile Learning Berbasis Android Sebagai Media Pembelajaran Program Aplikasi MYOB Accounting - Putri Intan Komariyah; Agung Listiadi (Universitas Cokroaminoto Palopo, 2022)
The purpose of this research is to develop student learning media by applying Android-based mobile learning to computer accounting subjects with the help of the MYOB application program on trading company materials at SMKN 6 Surabaya. The results of the analysis used are the results of the feasibility test of learning media, and are guided by the results of the assessment of learning media taken from media experts and material experts as well as student responses. This study uses a 4D model from Thiagarajan, but in this study it is limited to only three stages, namely Define, Design and Develop. The type of method chosen in this research is quantitative. In collecting data through media validation sheets, material expert validation sheets and student response questionnaires. This media experiment was conducted on 20 students of class XI Accounting and Finance at SMKN 6 Surabaya. Launching the research results, it can be stated that this android-based learning media is very feasible with the overall results having an average component value of 88.2%. This figure includes the feasibility of content, presentation, and media. The results of student responses indicate that this learning media is very feasible. The results of the students' responses show that this learning media is very good. According to the results of the feasibility of this product, it can be concluded that android-based learning media is very feasible to be used as a learning medium